Linear Discriminatory Analysis: A Patient Classifying for Research and Production Control - HALL, P.; HALLEN, B.; SELANDER, H. (Methods of Information in Medicine, 1971)
Administrative and medical information about the patient forms, in each case, a pattern, the complexity of which increases as the number of data grows. Even when the data are 4—5 in number, the human ability to recognize and distinguish between different patterns begins to fail, A mathematical method (linear discriminatory analysis) has been worked out. This system of analysis appears to provide opportunities of placing patients with the same or similar patterns in classes which are diagnostically, prognostically or therapeutically homogeneous.
Keywords: Patient Classification; Discriminatory Analysis; Medical Data Bank; Medical Record System J5; Anaesthesia Protocols; Anaesthssia Risk Groups